Storytelling as a didactic strategy for the production of texts in high school students - Romani-Pillpe, Guillermo (2022)
The objective of this research was to determine the effects of Storytelling as a didactic strategy for the production of texts in students of an institute in the city of Ica. The study included the participation of 68 students from the first semester of the Public Technological Higher Education Institute Federico Uranga from the Province of Pisco. The participants were chosen by an intentional capture, enrolled in the transversal course of Interpretation and Production of Texts. The research was a pre-experimental design and the statistical test used was Wilcoxon's T test. For the general hypothesis, the results show that the Agricultural Mechanics Study Program obtained a p <= 0.010. While the Food Industry Study Program obtained a p value <= 0.00; with similar results the Executive Secretariat Studies Program p <= 0.00, That is, the data obtained showed values lower than p < 0.05, accepting H1 and rejecting hypothesis H0. The results indicate that the application of Storytelling as a didactic strategy improves the production of texts. The study concludes that the application of Storytelling is effective and pertinent, respectively.